Slc2a10 knock-out mice deficient in ascorbic acid synthesis recapitulate aspects of arterial tortuosity syndrome and display mitochondrial respiration defects. (20th April 2020) - Boel, Annekatrien; Burger, Joyce; Vanhomwegen, Marine; Beyens, Aude; Renard, Marjolijn; Barnhoorn, Sander; Casteleyn, Christophe; Reinhardt, Dieter P; Descamps, Benedicte; Vanhove, Christian; van der Pluijm, Ingrid; Coucke, Paul; et al.
Abstract: Arterial tortuosity syndrome (ATS) is a recessively inherited connective tissue disorder, mainly characterized by tortuosity and aneurysm formation of the major arteries. ATS is caused by loss-of-function mutations in SLC2A10, encoding the facilitative glucose transporter GLUT10. Former studies implicated GLUT10 in the transport of dehydroascorbic acid, the oxidized form of ascorbic acid (AA). Mouse models carrying homozygous Slc2a10 missense mutations did not recapitulate the human phenotype. Since mice, in contrast to humans, are able to intracellularly synthesize AA, we generated a novel ATS mouse model, deficient for Slc2a10 as well as Gulo, which encodes for L-gulonolactone oxidase, an enzyme catalyzing the final step in AA biosynthesis in mouse. Gulo;Slc2a10 double knock-out mice showed mild phenotypic anomalies, which were absent in single knock-out controls. While Gulo;Slc2a10 double knock-out mice did not fully phenocopy human ATS, histological and immunocytochemical analysis revealed compromised extracellular matrix formation. Transforming growth factor beta signaling remained unaltered, while mitochondrial function was compromised in smooth muscle cells derived from Gulo;Slc2a10 double knock-out mice. Altogether, our data add evidence that ATS is an ascorbate compartmentalization disorder, but additional factors underlying the observed phenotype in humans remain to be determined.